Between Metaphor-Images and Visual Narratives: artistic methodologies driving Teaching and Research at the University (Revista Apotheke, 2024)
This article is based on on experiences in higher education to explore the use of artistic methodologies in educational research and teacher training, in line with the epistemological changes underway in academia. The main objective is to reflect on the challenges and contributions of these approaches to the teaching, learning and research processes. Supported by the educational perspective of visual culture (Hernández, 2011, 2013a; 2020) and Art-Based Methodologies (Hernández, 2013b; Dias, 2013; Irwin, 2013), we discuss issues related to non-verbal language as a catalyst for exploring themes in teaching and research. We conclude that deviating from the traditional text-centered academic logic towards the production of visual narratives opens up new and multiple possibilities for learning in contemporary times.
Keywords: images-methapor; visual narratives; artistic methodologies; teaching; academic research